Penilaian Status Daerah Aliran Sungai (Studi Kasus Sub Das Serang) - Mahmud Mahmud; Heru Joko; Sahid Susanto (Faculty of Agricultural Technology, Universitas Gadjah Mada, Yogyakarta, Indonesia, 2009)
Utilization of natural resources which does not consider the conservation of natural resources of the watershed will increase natural disasters such as landslides, erosion and sedimentation, flooding, and drought. To overcome the prob lem, government and communities have to manage the watershed so natural resources can be sustained. This research aims at studying the condition of the watershed hydrology and land use and socioeconomic of parameters, as well as determining the status of Serang sub watershed. The data collected were: hydrology (coefficient of river regime, coefficient of debit variance, the actual sediment, water quality and ground water), land (erosion and land use) and socio-economic (institutional and socio-economic). Results showed that coefficient of river regime of 69 represented the average category, coefficient of debit variance of 0.48 represented the bad category, the index utilization of water of 0.07 represented the good category, sedimentation of 0.03 mm/years represented the good category, water quality in term of physical as well as of chemical and biological represented the good category, and the fluctuation of groundwa ter represented the average category. The type of erosion based on the slope, soil solum, morfoerosion, quality of soil, and water conservation was categorized as normal. Based on socioeconomic factors with land dependency indicator was categorized as average; with the status of land ownership, watershed institution, norms, and the level of adoption of conservation technique indicators was categorized as good; with income population indicator was categorized as bad. To sum up, based on those parameters i.e. hydrology, land and socioeconomic parameters, status of Serang sub watershed was categorized as good.ABSTRAKPemanfaatan sumberdaya alam yang tidak memperhatikan konservasi sumberdaya alam DAS akan meningkatkan bencana alam seperti: tanah longsor, erosi dan sedimentasi, banjir, dan kekeringan. Untuk mencegahnya pemerin tah dan masyarakat perlu mengelola kawasan DAS sehingga sumberdaya alam bisa lestari. Penelitian ini bertujuan mengetahui kondisi pengelolaan DAS dari parameter hidrologi, lahan dan sosial ekonomi dan menentukan status DAS sub DAS Serang. Data yang dikumpulkan adalah data hidrologi (koefesien regim sungai, koefesien variasi debit, kandungan sedimen, kualitas air permukaan dan air tanah), lahan (erosi dan tata guna lahan) serta sosial ekonomi (kelembagaan dan sosial ekonomi). Berdasarkan hasil penelitian dari parameter hidrologi, lahan dan sosial ekonomi bahwa sub DAS Serang memiliki koefisien regim sungai (69) termasuk kategori sedang dan koefisien variasi debit air (0,48) termasuk kategori buruk, indeks penggunaan air (0,07) termasuk kategori baik, laju sedimentasi (0,03 mm/th) termasuk kategori baik, kualitas air dari segi fisik termasuk kategori sedang sampai baik, kualitas air dari segi kimia dan biologi termasuk kategori baik serta fluktuasi muka air termasuk kategori sedang. Erosi dengan memperhatikan kelas lereng, solum tanah, morfoerosi dan kualitas konservasi tanah termasuk kategori normal. Sedangkan faktor so sial ekonomi dengan indikator ketergantungan lahan termasuk kategori sedang, status pemilikan lahan, kelembagaan DAS, norma dan adopsi konservasi termasuk kategori baik serta pendapatan penduduk termasuk kategori buruk. Dengan memperhatikan faktor hidrologi, lahan dan sosial ekonomi maka status Sub DAS Serang dengan nilai 2,705 adalah masuk kategori baik.